Three encounters : Heidegger, Arendt, Derrida - Krell, David Farrell (Studies in Continental thought., 2023)
"In 1974, thirty-year-old philosopher and translator David Krell began corresponding and then meeting with Martin Heidegger and Hannah Arendt. Years later, he would meet Jacques Derrida and, through many letters and meetings, came to know him well. Drawing on unpublished correspondence and Krell's warmly told personal recollections, Three Encounters presents an intimate and highly insightful look at the lives and ideas of three noted philosophers as they neared the culmination of their careers. Three Encounters offers a chance for readers to encounter these three great philosophers and their ideas, not through the lens of their biographies, but as "people" known through their personal correspondence and Krell's recollections, demonstrating the entanglement of thought and the lived experience"--